Estudo da degradação dos pesticidas carbofurano, 2,4-d e metribuzim em solução aquosa através do processo de oxidação avançada - Silva, Luana de Morais e (2015)
The use of pesticides is necessary to provide the rapid increase in agricultural productivity and resilience. However, excessive use of these pesticides in the country and the world is a permanent risk of environmental pollution. The conventional physico-chemical or biological methods alone are not effective in the treatment of organic compounds dissolved in low concentrations, usually necessitating post-treatment. The Advanced Oxidation Processes (POAs) are based on the generation of hydroxyl radicals (HO *) highly reactive species that degrade organic pollutants in less complex compounds and can mineralize them completely, converting them to CO2 and H2O. In this work, the Advanced Oxidation Processes UV, UV/H2O2 and UV/Fe2+/H2O2 were used to evaluate the degradation of 2,4-D pesticide, metribuzin and furadan in aqueous solution. UV / Fe2 + / H2O2 in the degradation of different pesticides, furanda, 2,4-D and metribuzim. The degradation kinetics of pesticides during POA treatment were studied. The results of exposure after UV irradiation show that UV photolysis plays an important role in the degradation of these pesticides. The process UV/H2O2 process provided higher efficiency when compared to UV photolysis alone. The results indicate that when the concentration of oxidant H2O2 increases there is an increase in the degradation efficiency of the pesticides and the increase of the concentration of the oxidant influences the exposure time. From 10 mg/L of hydrogen peroxide was found to higher removal values of pesticides. Combination of Fe2+ and H2O2 for the studied concentrations does not display significantly better results compared to the process UV/H2O2 with concentration of 40mg/L. The degradation kinetics behaved pseudo-first order. For processes UV/H2O2 kinetic constants are positively correlated with the concentration of H2O2. The studies using UV-LED does not contribute to removal of pesticides since use wavelength higher than those reported in literature for the degradation of pesticides studied (UV-C).